Effect of Melamine Foam Cleaning on the Surface Condition of Composite Resin Artificial Teeth. Issue 8 (26th July 2013) - Tanaka, Rika; Kurogi, Tadafumi; Murata, Hiroshi
Abstract Purpose The purpose of this study was to examine the abrasive and cleaning effects of melamine foam and other cleaning agents on the surfaces of composite resin artificial tooth specimens. Materials and Methods A stained composite resin artificial tooth in a used denture was cleaned using a denture brush and melamine foam, and the stain removal effect was evaluated macroscopically. Next, 5 types of cleaning material (fourfold‐compression melamine foam, MEL; brush with water, BRU; denture dentifrice without abrasive, POL; denture dentifrice with abrasive, TAF; conventional dentifrice, AQU) and 15 plate‐shaped specimens made of composite resin for artificial teeth were used for wear tests. The surface roughness was measured using a laser scanning microscope. Furthermore, the surface properties were observed using a digital microscope. Surface roughness data were analyzed by two‐way ANOVA followed by Tukey's test. Results Artificial tooth stains that could not be removed by brushing became removable using melamine foam. With regard to surface roughness in the context of the wear test, significant differences were not indicated between MEL and POL, whereas BRU‐, TAF‐, and AQU‐treated specimens showed significantly increased surface roughness (p < 0.05). In the comparison among the cleaning materials, TAF‐ and AQU‐treated specimens showed significantly rougher surfaces than those treated with MEL, BRU, and POL (p < 0.05). Conclusions Macroscopic observations suggest that melamine foam would be effective for the removal of stains on composite resin artificial teeth. Traces of wear were not observed in specimens treated with melamine foam and the denture dentifrice not containing abrasives. It was suggested that these two materials would be desirable and useful to use for composite resin tooth cleaning.